Media policy and globalization - Chakravartty, Paula; Sarikakis, Katharine, 1970- (Media topics., 2006)
This volume takes a fresh look at media and communications policy and provides a comprehensive account of issues that are central to the study of the field. It moves beyond the 'specifics' of regulation, by examining policy areas that have proved to be of common concern for societies across different socio-economic realities. It also seeks to address profound gaps in the study of policy by demonstrating the centrality of historical, social and political context in debates that may appear solely technical or economistic. Media Policy and Globalization covers the institutional changes in the communications policy arena by examining the changing role of the state, technology and the market and the role of civil society. It discusses actual policy areas in broadcasting, telecommunications and the information society, and examines the often-overlooked normative dimensions of communications policy. Key Features: Provides a cross-disciplinary critical perspective of the politics of communications policy-making in a global context Explores new issues in communications policy such as ethical concerns and the 'internationality of policy' Useful for upper-level undergraduate students, graduate students and scholars of Communications and Media Studies, and International and Global Studies.